Computer‐Aided Design and Synthesis of 1‐{4‐[(3, 4‐Dihydroxybenzylidene)amino]phenyl}‐5‐oxopyrrolidine‐3‐carboxylic Acid as an Nrf2 Enhancer. Issue 5 (6th April 2018) - Kahremany, Shirin; Babaev, Ilana; Hasin, Pinhas; Tamir, Tigist Y.; Ben‐Zur, Tali; Cohen, Guy; Jiang, Zhengyu; Weintraub, Sagiv; Offen, Daniel; Rahimipour, Shai; Major, M. Ben; Senderowitz, Hanoch; et al.
Abstract: Invited for this month's cover is Prof. Arie Gruzman (Bar‐Ilan University) and collaborators who have developed an Nrf2 enhancer. This compound activated the Nrf2 transduction pathway and because of this the translation of dozens of antioxidant cytoprotective proteins in a dose‐ and time‐dependent manner and protected PC‐12 cells against oxidative stress. Considering the imbalance between production and elimination of oxidative species involved in the pathophysiology of many human diseases, this compound is a promising starting point for the development of novel therapeutics for the treatment of oxidative‐stress‐related diseases. Read the full text of the article at10.1002/cplu.201700539 . Abstract : "There is no doubt that our daily interactions to exchange ideas and discuss results promoted better scientific outcomes for this project." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI:10.1002/cplu.201700539 ).